Quality Control in Community Education as an Effort to Increase the Participation of Learners at the Marsudi Putra Tengku Yuk Youth Social Rehabilitation Center, Pekanbaru - Dinda Ovellia; Rahmat Fahmi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to comprehensively analyze the implementation of community education quality control as a strategy to increase the participation of learners at the Marsudi Putra Tengku Yuk Youth Social Development Center in Pekanbaru. The background of this research arises from the problems of low motivation, discipline, and active involvement of the residents in learning activities. To address these problems, the study uses a qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The results of the study indicate that the quality control implemented includes key aspects: program planning that aligns with the needs of the resident youth, as well as continuous evaluation of learning outcomes. These aspects have been proven to enhance learning motivation, foster a sense of responsibility, and strengthen the discipline of the residents. In addition, support from the center's management and facilitators also reinforces effectiveness of quality control.